Upaya Peningkatan Keaktifan Siswa Melalui Metode Kelompok Kecil Untuk Eksplorasi Pengamalan Nilai-Nilai Pancasila - Ega Prasetya; Wahdan Najib Habiby; Andi Arfianto (Departement of Mathematics Education, 2024)
The purpose of the study is to improve student’s activeness during learning process. Because researcher found that student’s activeness in the learning process could be much better if the method is suitable with the character of students. Subject of the research are 28 students. Type of the research is class action research. Procedure of the research consist of 4 steps. They are: planning, action, observation, and reflection. Data collection method used in the research is observation, interview and documentation. The result of the precycle, student’s activeness is on (56,25%). On the precycle, only 4 students that very active and 5 students active. 19 other students are on the level of less active. The result on the cycle 1 after the researcher implementing group discussion, student’s activeness is on (66,07%). It shows there is increase from the precycle to cycle 1. On the cycle 1, 6 students are very active and 10 students active, while 12 other students are on the level of less active. The result of cycle 2, researcher implementing small group discussion already. It shows student activeness got higher score (79,46%). On the cycle 2, 10 students are very active and 13 students active, while 5 other students are on the level of less active. There is significant increase from precycle being compared to cycle 2. Based on the result, researcher conclude that the usage of small group discussion is effective to increase student’s activeness from 56,25% to 79,46%.